Assessment for Learning: Perspectives, Beliefs and Practice of School Teachers in Vietnam - Hung, Le Thai; Ha, Le Thi Hoang; Vy, Nguyen Thi Phuong (VNU Journal of Science: Education Research; Vol 38 No 2DO - 10.25073/2588-1159/vnuer.4638, 2022)
Classroom assessment has been recognized as an inseparable component of teaching. Nowadays, besides the function of measuring the level of mastering learning objectives of students, educators and researchers are paying more attention on the benefits of facilitating learning that classroom assessment can bring about. This study was conducted basing on a survey on the school teachers’ perspectives, beliefs and practice of classroom assessment, particularly focusing on formative assessment strategies. The survey questionnaire was responded by over 500 primary and secondary teachers throughout the country. Assessment strategies which were investigated include: clarifying and sharing learning objectives, collecting learning evidences, giving feedback, making students to be the owners of learning. Besides descriptive statistics results, the findings show a relationship between teachers’ perspectives and beliefs and their practice of classroom assessment.